Transferts culinaires gréco-allemands dans la Grèce du roi Othon : - Marie-Élisabeth Mitsou (Cahiers Balkaniques)
This paper examines the culinary experiences of four foreign women living in Greece under the rule of King Otto. In their letters and diaries (1834-1853) they describe their daily tribulations and their efforts to adapt to the available produce and tastes of a poor, semi-oriental country of South Europe.